2021
DOI: 10.1158/2326-6066.cir-20-1002
|View full text |Cite
|
Sign up to set email alerts
|

A Fusion Protein Complex that Combines IL-12, IL-15, and IL-18 Signaling to Induce Memory-Like NK Cells for Cancer Immunotherapy

Abstract: Natural killer (NK) cells are a promising cellular therapy for cancer, with challenges in the field including persistence, functional activity, and tumor recognition. Briefly, priming blood NK cells with recombinant human (rh)IL-12, rhIL-15, and rhIL-18 (12/15/18) results in memory-like NK cell differentiation and enhanced responses against cancer. However, the lack of available, scalable Good Manufacturing Process (GMP)–grade reagents required to advance this approach beyond early-phase clinical trials is lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 58 publications
4
44
0
Order By: Relevance
“…Due to their potent anti-tumor functions, the enhancement of NK cell activity against cancer is currently the focus of multiple therapeutic strategies. These include CAR-NK based approaches ( 11 , 12 ), agonistic antibodies ( 13 ), cytokine mediated stimulation ( 14 ) and checkpoint inhibitors ( 15 ). In addition to these direct approaches, NK cells can also contribute to the efficacy of other cancer therapies via the detection of altered activating and inhibitory ligand expression patterns on stressed tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their potent anti-tumor functions, the enhancement of NK cell activity against cancer is currently the focus of multiple therapeutic strategies. These include CAR-NK based approaches ( 11 , 12 ), agonistic antibodies ( 13 ), cytokine mediated stimulation ( 14 ) and checkpoint inhibitors ( 15 ). In addition to these direct approaches, NK cells can also contribute to the efficacy of other cancer therapies via the detection of altered activating and inhibitory ligand expression patterns on stressed tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few evidences supporting this hypothesis was reported by Ni et al., who found that the conserved non-coding sequence 1 (CNS1) in the Ifng locus of IL-12/15/18-preactivated NK cells was demethylated 11 days after transferring these cells into RAG -/- γc -/- mice ( 60 ). Demethylated CNS1 in the Ifng locus was also found in human CIML NK cells after a resting period of 14 days ( 54 ). Additionally, it has been reported that the histone methyltransferase EZH2 plays a crucial role in CIML NK cells, since its pharmacological inhibition with UNC1999 limited the enhanced IFNγ production following IL-12/18-restimulation ( 61 ).…”
Section: Cytokine-induced Memory-like (Ciml) Nk Cellsmentioning
confidence: 99%
“…Specifically, IL-12/15/18-stimulated NK cells upregulate the expression of certain nutrient transporters, including the transferrin receptor CD71, the heavy subunit of multiple heterodimeric amino acid transporters CD98, and glucose transporters GLUT1 and GLUT3, and retain an elevated expression of CD98 and GLUT1 after a resting period ( 52 ). Moreover, upon IL-12/15/18 stimulation NK cells increase their metabolic activity and retain a metabolic profile shifted towards glycolysis for at least 7 days ( 52 54 ). Interestingly, inhibiting glycolytic activity with 2-DG during IL-12/15/18 stimulation resulted in a lower IFNγ production, both immediately after stimulation with cytokines and after a resting period of 6 days ( 53 , 55 ).…”
Section: Cytokine-induced Memory-like (Ciml) Nk Cellsmentioning
confidence: 99%
“…In addition, IL-15 can increase the infiltration of NK cells in the tumor ( 190 ) and improve the survival rate in the treatment of GC liver metastasis–bearing mice ( 191 ). Primer of blood NK cells with recombinant human (rh)IL-12, rhIL-15, and rhIL-18 (12/15/18) can lead to memory-like NK cell differentiation and enhance tumor response ( 192 ). At the same time, increasing the immune clearance of NK cells against tumors can also play an anti-tumor effect.…”
Section: Immunotherapy Targeting Nk Cellsmentioning
confidence: 99%